Effects of the proteasome inhibitor, bortezomib, on cytodifferentiation and mineralization of periodontal ligament cells. (20th June 2014) - Kitagaki, J.; Miyauchi, S.; Xie, C. J; Yamashita, M.; Yamada, S.; Kitamura, M.; Murakami, S.
Abstract : Background and Objective: The proteasome inhibitor, bortezomib, is known to induce osteoblastic differentiation in a number of cell lines, such as mesenchymal stem cells and osteoblastic precursor cells. As periodontal ligament (PDL) cells are multipotent, we examined whether bortezomib may induce the differentiation of PDL cells into hard‐tissue‐forming cells. Material and Methods: A mouse PDL clone cell line, MPDL22 cells, was cultured in mineralization medium in the presence or absence of bortezomib. Expression of calcification‐related genes and calcified‐nodule formation were evaluated by real‐time PCR and Alizarin Red staining, respectively. Results: Bortezomib increased the expression of calcification‐related mRNAs, such as tissue nonspecific alkaline phosphatase isoenzyme ( ALPase ), bone sialoprotein ( Bsp ), runt‐related transcription factor 2 ( Runx2 ) and osteopontin, and calcified‐nodule formation in MPDL22 cells. These effects were induced, in part, by increasing the cytosolic accumulation and nuclear translocation of β‐catenin, leading to an increase in expression of bone morphogenetic protein ( Bmp ) ‐2, ‐4 and ‐6 mRNAs. In addition, bortezomib enhanced BMP‐2‐induced expression of Bsp and osteopontin mRNAs and increased calcified‐nodule formation in MPDL22 cells. Conclusion: Bortezomib induced cytodifferentiation and mineralization of PDL cells by enhancing the accumulation of β‐catenin within the cytosol and the nucleus and increasing the expression of Bmp‐2, ‐4 and ‐6 mRNAs. Moreover, bortezomib enhanced the BMP‐2‐induced cytodifferentiation and mineralization of PDL cells, suggesting that bortezomib may be efficacious for use in periodontal regeneration therapy.